WATER RESOURCES OF UZBEKISTAN - Nurieva Samira Shukhratovna (Web of Journals Publishing, 2024)
The article provides information about water resources of Uzbekistan, annual water consumption in the country, drinking water supply problems, solutions, current and planned work to provide drinking water in Uzbekistan.
Keywords: Air, water resources, annual water consumption, temperature, water supply, financing.